2022
DOI: 10.1088/1748-9326/ac939c
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous controls on lake color and trends across the high-elevation U.S. Rocky Mountain region

Abstract: Global change may contribute to ecological changes in high-elevation lakes and reservoirs, but a lack of data makes it difficult to evaluate spatiotemporal patterns. Remote sensing imagery can provide more complete records to evaluate whether consistent changes across a broad geographic region are occurring. We used Landsat surface reflectance data to evaluate spatial patterns of contemporary lake color (2010-2020) in 940 lakes in the U.S. Rocky Mountains, a historically understudied area for lake water qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Lake-specific characteristics reveal that lakes improving in water quality were in more developed and less forested catchments, as well as at lower elevations. These results are consistent with studies on water clarity , lake color (Oleksy et al, 2022), and chlorophyll-a (Wilkinson et al, 2022), that highlight improvements in water quality metrics over the same time period. These trends have been hypothesized to be the result of management actions or restoration projects (Wilkinson et al, 2022), although we lacked the information to make conclusions about the mechanisms of these trends.…”
Section: Productivity Trendssupporting
confidence: 90%
See 3 more Smart Citations
“…Lake-specific characteristics reveal that lakes improving in water quality were in more developed and less forested catchments, as well as at lower elevations. These results are consistent with studies on water clarity , lake color (Oleksy et al, 2022), and chlorophyll-a (Wilkinson et al, 2022), that highlight improvements in water quality metrics over the same time period. These trends have been hypothesized to be the result of management actions or restoration projects (Wilkinson et al, 2022), although we lacked the information to make conclusions about the mechanisms of these trends.…”
Section: Productivity Trendssupporting
confidence: 90%
“…manuscript submitted to Water Resources Research lakes have been shown to be increasing in the same metric over the past 40 years (Wilkinson et al, 2022). In addition, a minority of lakes (13%) in the Rocky Mountain region have shown to be shifting from blue to greener wavelengths during this time (Oleksy et al, 2022). With our analysis, we show that concerns regarding the widespread intensification of algal blooms are not captured in our analysis of chlorophyll-a and trophic state.…”
Section: Productivity Trendsmentioning
confidence: 73%
See 2 more Smart Citations
“…Satellite images have been utilized to investigate spatial distributions of lake color (Giardino et al., 2019; Lehmann et al., 2018; Topp et al., 2021; Yang et al., 2022). However, temporal shifts and trends in lake color and relevant drivers are rarely documented (Kuhn & Butman, 2021; Lehmann et al., 2019; Oleksy et al., 2022).…”
Section: Introductionmentioning
confidence: 99%